Multi-material additive manufacturing in architecture and construction: A review. (January 2022) - Pajonk, Adam; Prieto, Alejandro; Blum, Ulrich; Knaack, Ulrich
Abstract: Multi-Material Additive Manufacturing (MMAM) is an emerging manufacturing approach that is gaining interest in architecture and construction as an expansion of Additive Manufacturing. Hereby, different materials or material properties are combined in a single additive process in order to create objects that are composed of multiple materials. Ultimately, this approach introduces a new way of manufacturing and building, where assembly is no longer a necessity in order to combine multiple materials. Moreover, different potentials can be derived from the use of MMAM. Leading towards components with heterogeneous material composition and a high degree of adaption towards structural, environmental, and design criteria. This work provides an overview of the current state of MMAM in architecture and construction. Different processes and materials which have been reported are discussed and potentials, which emerge through the use of MMAM are described using specific use-cases. Highlights: An overview of processing methods and materials is provided. The identified approaches were classified according to the processing method. Published applications for structural and non-structural building components are collected. Potentials of Multi-Material Additive Manufacturing in architecture and construction are presented.